Increasing students' creative thinking skills at 11th grade of mathematics and natural sciences 5, Senior High School 42 Jakarta on subject of Temperature and Heat by applying discovery learning model - Serevina, V; Sarah, A L; Risniawati, M; Andriana, W (Journal of physics. Conference series, 2020)
The purpose of this research is to increase the student's creative thinking skills by applying Discovery Learning on subject of Temperature and Heat subject. This research was done by July 2018 to November 2018. The method used on this research is Class Action Research (CAR) method which was done within two cycles with Planning, Acting, Observing, and Reflecting stages. The aspects that measured on this research are the creative thinking skill which covering the aspect of Fluency, Flexibility, Elaboration, and Originality. Syntax of discovery learning model that applied in this research is stimulation, problem statement, data collection, data processing, verification, and generalization. The total score of creative thinking skill in cycle 1 was 54,35%, in cycle 2 was 60,65%. So, the average score of the skill to think creatively was 57,5%, refer to table 1, the student's way in thinking creatively were "enough creative". The pretest was been held obtained that average results of students score was 55 and the posttest results was 73. On post test results 73 known that student has been reached minimal completeness of physics subject as big as 70 refer to the rules from Senior High School 42 Jakarta. It can be concluded that students'creative thinking skills has increased by applying Discovery Learning model on temperature and heat subject..